Evaluation of PVA/dextran/chitosan hydrogel for wound dressing. Issue 1 (January 2019) - Lin, Shin-Ping; Lo, Kai-Yin; Tseng, Tien-Ni; Liu, Jui-Ming; Shih, Ting-Yu; Cheng, Kuan-Chen
Developing a multiple functional wound dressing suitable for different stages of wound healing is important for patients with special wound such as burn or decubital ulcers. In this study, poly (vinyl alcohol) (PVA), dextran, and chitosan are integrated to produce ideal wound dressing where glutaraldehyde (GA) is used as the cross-linker. The result demonstrated that 6% PVA hydrogel with 0.25% chitosan was found to provide antimicrobial ability. The PVA/chitosan hydrogel combined with 4% dextran utilizing GA cross-linking also presents the high cell proliferation ability, which suggests that the hydrogel is potential as a wound dressing. In the following physical analyses, the addition of chitosan and dextran appeared to promote the thermostability, mechanical properties, water retention, and moisturizing ability in the PVA hydrogel. In conclusion, the PVA/chitosan/dextran hydrogel has promising potential such as high water content, antimicrobial property, and well cell proliferation, which can be applied to wound healing application.